Learning Targets: Policy Paradigms and State Responses to the Anticorruption Transnational Advocacy Network Campaign in Guatemala. (February 2022) - Fuentes, Alberto
ABSTRACT: Scholarship on Transnational Advocacy Networks (TANs) increasingly recognizes that even weak states targeted by TANs may respond, and subvert, transnational norm socialization campaigns. It examines both the conditions conducive to such responses and the range of policy instruments available to these states. Yet this emerging work lacks a robust, contextualized account for how states devise the strategy and the content of their responses. This article builds on the policy-learning literature to elucidate the process through which states construct their antiTAN approaches. It suggests that states' policy paradigms in the field of domestic security largely shape those responses, with different paradigms offering distinct priorities and instruments. The comparison of the divergent impact of the Guatemalan state's contrasting responses to two similar legal-political challenges, undertaken in the context of the same anticorruption TAN campaign, illustrates the argument.